’The Way You Feel Can Either Get in The Way or Get You on The Way’ A Systematic Review of Emotional Intelligence (International Journal of Scientific Research in Science and Technology, 2024)
The study on emotional intelligence in adolescents is a well-researched area that focuses on both the continuity and change of distinct components. This research presents a comprehensive analysis of existing literature on the topic of “Emotional intelligence among adolescents”. The publications used for this review study were obtained from databases like Elsevier, JStore, Wiley Online, Google Scholar, Tylor and Francis and others by using the search phrase “emotional intelligence among adolescents”. A systematic search was conducted in journals spanning the years 2000 to 2023, resulting in the retrieval of a total of 1152 publication out of which 1005 articles fulfilled the selection criteria . This article offers the findings derived from a comprehensive evaluation of scholarly publications in the different journals. Asia ranks first in terms of both publishing outlets and geographical context, according to the results. The majority of the studies used a qualitative technique and employed online data collection with a worldwide scope. Future research should focus on both domestic as well as global levels. In order to tackle the difficulties related to emotional intelligence among adolescents. It is imperative to publish a greater number of articles from varied background.